Telling right from wrong in life: cellular quality control - Stoecklin, Georg; Bukau, Bernd (Nature reviews, 2013)
An astounding ability to discriminate functional molecules from a range of unsuitable molecules is the cornerstone of cellular physiology. In all living cells, a hierarchy of communicating mechanisms directed at identifying, isolating, removing or repairing damaged molecules continuously monitors and maintains genomic integrity and cellular homeostasis, ensuring survival under changing and adverse conditions. This network interconnects with cytoprotective processes, which act preventively to avoid damage before it occurs. Altogether, this represents a massive evolutionary investment in cellular quality control. Four articles in this issue of Nature Reviews Molecular Cell Biology offer insights into emerging aspects of the cellular quality control network relating to RNA and proteins.